Augmented reality in support of Industry 4.0—Implementation challenges and success factors - Masood, Tariq; Egger, Johannes (Robotics and computer-integrated manufacturing, 2019)
•Augmented reality (AR) is a central part of Industry 4.0 or similar initiatives.•Providing guidance on which aspects industry should focus on to ensure AR implementation success.•Technology context and organisational fit are key success factors for the AR implementation.•User barrier and external support do not significantly influence the AR implementation success.•While technological aspects are important, organisational issues are more relevant for industry. Industrial augmented reality (AR) is an integral part of Industry 4.0 concepts, as it enables workers to access digital information and overlay that information with the physical world. While not being broadly adopted in some applications, the compound annual growth rate of the industrial AR market is projected to grow rapidly. Hence, it is important to understand the issues arising from implementation of AR in industry. This study identifies critical success factors and challenges for industrial AR implementation projects, based on an industry survey. The broadly used technology, organisation, environment (TOE) framework is used as a theoretical basis for the quantitative part of the questionnaire. A complementary qualitative part is used to underpin and extend the findings. It is found that, while technological aspects are of importance, organisational issues are more relevant for industry, which has not been reflected to the same extent in literature.